“They Were Really Looking for a Male Leader for the Building”: Gender, Identity and Leadership Development in a Principal Preparation Program - Burton, Laura J.; Weiner, Jennie M. (Frontiers in Psychology, 2016)
This study utilized a comparative case study analysis to investigate how gender influenced the experiences of participants in a leadership development program (principal preparation program) designed to lead public K-12 schools identified as requiring turnaround. We closely focused on two participants, a man and a woman, and compared the ways each participant made meaning of his/her experiences as developing leaders in the program. Although both participants conceptualized effective leadership in similar communally-oriented ways, the way they came to construct their identities as leaders varied greatly. These differences were largely influenced by different and, what appeared to be, gendered feedback occurring during the program and when participants entered the job market.